2017
DOI: 10.1177/0021998317722401
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical energy harvesting using polyurethane/lead zirconate titanate composites

Abstract: The microelectromechanical systems invade gradually the market with applications in many sectors of activity. Developing these micro-systems allows deploying wireless sensor networks that are useful to collect, process and transmit information from their environments without human intervention. In order to keep these micro-devices energetically autonomous without using batteries because they have a limited lifespan, an energy harvesting from ambient vibrations using electrostrictive polymers can be used. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Different mixtures of graphene and graphene oxide as reinforcements for PU have been studied by many researchers in previous years and have shown remarkable improvements in various properties . Other popular choices over the years for reinforcing particles for PU have been metallic powders, ceramics particles, nanoclay, natural clays, modified sand etc . Among these different kinds of reinforcements, TEMs of different forms of natural clays embedded in the PU matrix from a previous study are shown in Figure .…”
Section: Puf Core Sandwich Structuresmentioning
confidence: 99%
“…Different mixtures of graphene and graphene oxide as reinforcements for PU have been studied by many researchers in previous years and have shown remarkable improvements in various properties . Other popular choices over the years for reinforcing particles for PU have been metallic powders, ceramics particles, nanoclay, natural clays, modified sand etc . Among these different kinds of reinforcements, TEMs of different forms of natural clays embedded in the PU matrix from a previous study are shown in Figure .…”
Section: Puf Core Sandwich Structuresmentioning
confidence: 99%
“…On the other hand, the experimental setup used in this study has been explained in detail in a previous publication. 18 However, its working principle is shortly resumed in the following. The experimental setup allows making the energy harvesting tests using the PU-50-vol%-PZT composites.…”
Section: Methodsmentioning
confidence: 99%
“…Modeling the effect of piezoelectric materials is written in the form of the following two fundamental equations. The piezoelectric constitutive equations of direct and converse effects are given below [14]:…”
Section: Piezoelectric Harvested Current Modelmentioning
confidence: 99%
“…Recently, researchers investigated porous piezoelectric polymers consisting of an ionized cellular polypropylene film made by a chemical elaboration method using nitrogen gas [13]. Excellent piezoelectric coefficients up to 2000 pC/N for specific morphologies and mechanical conditions comparably higher than those of piezoceramics were identified [14,15]. In order to demonstrate the ability of the porous piezoelectric polymers in a harsh environment, Zhong et al [16] fabricated PET/EVA/PET laminated films and ionized them by a corona charging method.…”
Section: Introductionmentioning
confidence: 99%